2017
DOI: 10.1038/srep43787
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Epicardial Adipose Tissue Extracellular Matrix Remodeling in Patients with Severe Ischemic Cardiomyopathy: Insight from Comparative Quantitative Proteomics

Abstract: There is ample evidence indicating that epicardial adipose tissue (EAT) volume and thickness is positively associated with coronary artery disease (CAD). However, the exact pathological changes in the human EAT after myocardial ischemia remains largely unclear. In the current study, we applied a comparative quantitative proteomics to elucidate the altered biological processes in the EAT of ischemic cardiomyopathy (ICM) patients. A total of 1649 proteins were successfully quantified in our study, among which 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…In fact, in line with other fat depots [56,57], not only extracellular matrix proteins are remarkably increased in EAT in cardiac pathological conditions [58], but EAT may also induce fibrosis in the neighboring myocardium through the secretion of profibrotic mediators including inflammatory cytokines, growth factors and matrix metalloproteinases [59,60] (Fig. 1).…”
Section: The Emerging Role Of Eat In Cardiac Arrhythmiasmentioning
confidence: 99%
“…In fact, in line with other fat depots [56,57], not only extracellular matrix proteins are remarkably increased in EAT in cardiac pathological conditions [58], but EAT may also induce fibrosis in the neighboring myocardium through the secretion of profibrotic mediators including inflammatory cytokines, growth factors and matrix metalloproteinases [59,60] (Fig. 1).…”
Section: The Emerging Role Of Eat In Cardiac Arrhythmiasmentioning
confidence: 99%
“…In our study, we also observe differential regulation of some metabolic enzymes or components of the respiratory chain; however, the impact is too diffuse to be observed as in GO‐ enrichment analysis. Similarly, Jiang et al report an impact of ICM on metabolic enzymes, albeit without direct comparison to DCM . Ortega et al showed endoplasmic reticulum biology is differentially affected between ICM and DCM; our global approach lacks the methodological focus to investigate this aspect.…”
Section: Resultsmentioning
confidence: 93%
“…Similarly, Jiang et al report an impact of ICM on metabolic enzymes, albeit without direct comparison to DCM. 32 Ortega et al showed endoplasmic reticulum biology is differentially affected between ICM and DCM 33 ; our global approach lacks the methodological focus to investigate this aspect.…”
Section: Comparison Of Pre-lvad Proteome Profiles Of Ischemic and Dmentioning
confidence: 99%
“…were performed on a TripleTOF 5600+ System coupled with an Ultra 1D Plus nano-liquid chromatography device (SCIEX) as previous reported (45). Dried peptides were dissolved in 0.1% formic acid, 2% acetonitrile and 98% H 2 O.…”
Section: Liquid Chromatography-mass Spectrometry (Lc-ms)/ms and Data mentioning
confidence: 99%
“…A total of 90 proteins are differentially expressed in the spinal cord after IR injury. To identify the differentially expressed proteins in the spinal cord that are regulated by myocardial injury, a filtering rule was set as previously reported (41,45), to screen those differentially expressed proteins: Proteins with 50% change of ratio in each replicate, or P<0.05 in each replicate and additionally 50% change of average ratio, were considered to be differentially expressed. Among the whole quantitative dataset, 33 spinal cord proteins were found to be upregulated in IR rats, whereas 57 proteins were downregulated ( Fig.…”
Section: Proteomics Data Overviewmentioning
confidence: 99%